Water resources management - Asean-EEC Seminar on Water Resource Management : Problems and Prospects (1983 : Kuala Lumpur); Malaysia. Kementerian Sains, Teknologi dan Alam Sekitar. Bahagian Alam Sekitar (Kuala Lumpur : Ministry of Science, Technology and Environment Malaysia, 1983)
28